The Effect of Calcination Temperature on The Quality of Quicklime from Different Limestone Mines in West Sumatera, Indonesia - Reni Desmiarti; Ellyta Sari; Firdaus Firdaus; Erda Desfitri; Amelia Amir; Inva Salsabil; Maulana Rosadi; Nofri Naldi (Journal of Applied Agricultural Science and Technology, 2022)
Quicklime is a widely used industrial chemical and its characteristics may be affected by the limestone characteristics and calcination temperature. The present study investigated the quicklime characteristics obtained from limestone after calcination at different temperatures (800, 900, and 1000 ℃) from six geological-different mines in West Sumatera, Indonesia. X-ray fluorescence (XRF) analysis was performed to characterize the elemental compositions in limestone and quicklime. The stoichiometric evaluation was examined to compare the obtained carbon dioxide (CO2) from experimental and theoretical results during calcination. Based on elemental composition from XRF analysis, all the investigated limestones are very pure limestones, with impurities of less than 1%. The level of calcium oxide (CaO) after calcination at 1000℃ increased to more than 90% for all investigated limestone. The obtained CaO and CO2 mass after calcination at 1000℃ for 5 h were more than 70 and 60 grams, respectively. However, the experimental results on CaO and CO2 mass were 5–12% less than theoretical mass, reflecting the partial decomposition of calcium carbonate during the calcination process.